2019
DOI: 10.1080/14786419.2019.1596095
|View full text |Cite
|
Sign up to set email alerts
|

The complete stereochemistry of the antibiotic candicidin A3 (syn. ascosin A3, levorin A3)

Abstract: Herein, the stereostructure of the aromatic heptaene macrolide (AHM) antifungal antibiotic candicidin A3 (syn. ascosin A3, levorin A3) has been established upon the 2D NMR studies, consisting of DQF-COSY, TOCSY, ROESY, HSQC & HMBC experiments, as well as upon extensive molecular dynamics simulations. The geometry of the heptaenic chromophore was defined as: (22E, 24E, 26Z, 28Z, 30E, 32E, 34E). The previously unreported absolute configuration of the chiral centres of candicidin A3 was established as: (3R,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This procedure was previously successfully applied for the definition of stereochemistry of almost 20 polyene macrolides and their derivatives, including: the candicidins [ 17 , 18 , 19 , 20 ], rimocidin [ 21 ], candidin [ 22 ], mycoheptin A2 [ 23 ], etc. In this standardized approach, DQF-COSY and TOCSY experiments have allowed tracing of connectivities within isolated proton spin systems, separated by quaternary carbon atoms and oxygen-involving lactone and glycosidic bonds.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure was previously successfully applied for the definition of stereochemistry of almost 20 polyene macrolides and their derivatives, including: the candicidins [ 17 , 18 , 19 , 20 ], rimocidin [ 21 ], candidin [ 22 ], mycoheptin A2 [ 23 ], etc. In this standardized approach, DQF-COSY and TOCSY experiments have allowed tracing of connectivities within isolated proton spin systems, separated by quaternary carbon atoms and oxygen-involving lactone and glycosidic bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed NMR studies revealed that, in contrary to the NMR data on the partricin A and partricin B methoxycarbonylmethylamide derivatives [8][9][10], all the 3 J H,H coupling constants within the double bonds were no lower than 15.1 Hz and no higher than 15.6 Hz, thus determining the E geometry of the entire chromophore systems. The chemical shifts of all the olefinic carbons (C22-C35) ranged between 130 and 137 ppm, which strongly suggested the E geometries of all the double bonds within the chromophores, since no shielding γ-effects were observed for the C27/C30 and C29/C32 pairs [9,16,22]. Moreover, rich sets of ROEs between the protons of the C2-C13 and C22-C35 fragments were recorded (Figure 3), as well as two uninterrupted ROE pathways, incorporating even-and odd-numbered olefinic protons (see Appendix A section, Table A1).…”
Section: Nmr Studies On Iso-partricin a And Bmentioning
confidence: 95%
“…The native partricin complex was derivatized into its N-acetyl methyl ester via series of simple reactions. This procedure, developed at our department, is a well-established approach for the elucidation of constitution and/or stereochemistry of polyene macrolides, using NMR techniques [5,16,[20][21][22], and, as an option, could be followed in order to facilitate purification of studied antibiotic molecules and enhance their solubility in standard NMR solvents. Later, the resulting methyl ester of N-acetylpartricin (referred to as partricin*) was exposed to moderate UV-VIS radiation of λ = 365 nm.…”
Section: Nmr Studies On Iso-partricin a And Bmentioning
confidence: 99%
See 2 more Smart Citations